2013
DOI: 10.1016/j.ijrobp.2012.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Disease Control After Reduced Volume Conformal and Intensity Modulated Radiation Therapy for Childhood Craniopharyngioma

Abstract: PURPOSE To estimate the rate of disease control after conformal radiation therapy using reduced clinical target volume (CTV) margins and determine factors that predict for tumor progression. METHODS AND MATERIALS Eighty-eight children (median age 8.5 years, range 3.2–17.6 years) received conformal or intensity-modulated radiation therapy between 1998 and 2009. This included those prospectively treated from 1998 to 2003 using a 10 mm CTV, defined as the margin surrounding the solid and cystic tumor targeted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 19 publications
(22 reference statements)
1
34
0
Order By: Relevance
“…As radiation becomes more conformal and the use of particle therapy (e.g., PBT) becomes more prevalent, monitoring and accounting for cyst changes during treatment are essential to avoid underdosing target structures or overdosing critical structures. 17-23 Furthermore, cystic components of craniopharyngiomas can also change after RT is completed. However, both the incidence and implications of such changes are unclear and complicate the evaluation of treatment response.…”
Section: Introductionmentioning
confidence: 99%
“…As radiation becomes more conformal and the use of particle therapy (e.g., PBT) becomes more prevalent, monitoring and accounting for cyst changes during treatment are essential to avoid underdosing target structures or overdosing critical structures. 17-23 Furthermore, cystic components of craniopharyngiomas can also change after RT is completed. However, both the incidence and implications of such changes are unclear and complicate the evaluation of treatment response.…”
Section: Introductionmentioning
confidence: 99%
“…In a phase II trial of conformal radiation therapy in pediatric craniopharyngioma, nearly half the patients demonstrated cystic enlargement during therapy; 13 of 28 patients required cyst aspiration at least once during treatment and in three the tumor change was significant enough to require revision of the treatment plan (Merchant et al, 2006). In another study evaluating tumor control after conformal and intensity-modulated radiation therapy using a reduced planning volume, cyst enlargement requiring a change in treatment plan occurred in 22 of 88 cases (Merchant et al, 2013). A change in the solid component was not observed in any patient.…”
Section: Historical Overview and Role Of Cyst Drainagementioning
confidence: 99%
“…Experience with 3D conformal radiation is also excellent with most modern series, suggesting disease control rates between 80e100% (Stripp et al, 2004;Jalali et al, 2005;Merchant et al, 2006;Kiehna and Merchant, 2010). Although less data on outcomes for IMRT are available, published studies also report favorable outcomes (Merchant et al, 2013). Data for proton therapy are even more scarce, but Winkfield et al reported 100% local control for 24 patients at a median follow-up of 40.5 months (Winkfield et al, 2009).…”
Section: Clinical Treatment and Outcomesmentioning
confidence: 99%